A Study on Gender and Behavior Differences Influencing On Online Purchasing In Tirunelveli District (International Journal of Food and Nutritional Sciences, 2022)
The development of Internet has resulted in enormous business prospects and opportunities and given new direction to traditional commercial activities. E-commerce emerged as the need of the hour. The business-to-consumer (B2C) is the most visible and prominent progeny of e-commerce. B2C is a commercial process that starts with companies and ends with end consumers. Online shopping is an emerging area in the field of E-Business and is surely going to be the future of shopping in the world. The benefits of online shopping are well known. On-line shopping in India is significantly affected by various demographic factors like age, gender, marital status, educational qualification, occupation and income. Substantial amount of research work has been carried out on all these areas. The impact of these factors on online shopping behaviour is fascinating to say the least. But the most mysterious of them all is the impact of gender on the acceptance or rejection of online shopping. Do men and women behave differently during the online shopping process or do they exhibit same kinds of behaviour during this process? This article will try to throw some light on the extremely valuable but often neglected role of gender in the online shopping behaviour of consumers. Recently, the diffusion of the Internet as a retail and distribution channel has undergone a great growth in India. This paper presents an empirical investigation on the effects of gender differences on online buying in Tirunelveli District. The study explored gender differences among twelve factors concerning the online buyer for both Male and Female in Tirunelveli District. For data collection and final testing of the model a well-structured questionnaire was designed and hosted. The researcher collected 147 respondents sent their answer out of 150 questionnaires. With regard to factors and consistent with using t-student test.